2021
DOI: 10.3389/frobt.2020.595862
|View full text |Cite
|
Sign up to set email alerts
|

An Assistive Soft Wrist Exosuit for Flexion Movements With an Ergonomic Reinforced Glove

Abstract: Soft exosuits are a promising solution for the assistance and augmentation of human motor abilities in the industrial field, where the use of more symbiotic wearable robots can avoid excessive worker fatigue and improve the quality of the work. One of the challenges in the design of soft exosuits is the choice of the right amount of softness to balance load transfer, ergonomics, and weight. This article presents a cable-driven based soft wrist exosuit for flexion assistance with the use of an ergonomic reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…[ 505 ] Perhaps the most common controller in everyday life is a printed circuit board, [ 506 ] made mainly from a composite matrix of rigid plastic. Nascent research has focused on making use of the rigidity of plastics for the grounding of torques in wearable exosuits, [ 507 ] developing computational inverse designs of surface topologies for the aforementioned inflatable flexible sheets, [ 508 ] and incorporating an array of kirigami‐based grippers for manipulating delicate objects. [ 509 ] The appeal of plastics generally comes from low‐cost fabrication, availability, electrically insulating characteristics, and a breadth of structural properties.…”
Section: Resultsmentioning
confidence: 99%
“…[ 505 ] Perhaps the most common controller in everyday life is a printed circuit board, [ 506 ] made mainly from a composite matrix of rigid plastic. Nascent research has focused on making use of the rigidity of plastics for the grounding of torques in wearable exosuits, [ 507 ] developing computational inverse designs of surface topologies for the aforementioned inflatable flexible sheets, [ 508 ] and incorporating an array of kirigami‐based grippers for manipulating delicate objects. [ 509 ] The appeal of plastics generally comes from low‐cost fabrication, availability, electrically insulating characteristics, and a breadth of structural properties.…”
Section: Resultsmentioning
confidence: 99%
“…However, the preservation of the freedom of movement offered by soft exosuits, as well as their comfort, depends on ergonomically appropriate design. Indeed, several recent works have focused on the design of ergonomic soft exoskeletons to minimize user discomfort (Andrikopoulos et al, 2015;Varghese et al, 2018;Choi et al, 2019;Chiaradia et al, 2021). These studies showed how the combination of textile fibers, 3D printed plastic materials and sometimes even metal parts, should be carefully designed to offer appropriate ergonomics and avoid possible limitations of the device's functionality.…”
Section: Soft Exoskeleton Designsmentioning
confidence: 99%
“…Chiaradia et al [63] developed a cable-based soft wrist exosuit. The device reduces muscle fatigue and allows it to lift small weights of up to 3 kg.…”
Section: Wristmentioning
confidence: 99%